2022
DOI: 10.18559/ebr.2022.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Stock returns and liquidity after listing switch on the Warsaw Stock Exchange

Abstract: The aim of the article is to evaluate the market reaction to the change of listing venue of companies moving from the alternative market to the regulated market of the Warsaw Stock Exchange. To do so, we investigated 71 switches, and their effect on market returns and liquidity. While the transfer itself creates a negative market reaction, the announcement of the transfer of a company and the institutional confirmation by the supervision of the company’s readiness for this transfer resulting from the approval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Such results were confirmed in a broader sample, i.e. 71 companies by Podedworna-Tarnowska and Kaszyński (2022), who showed also the liquidity improvement of shares after the listing switch. Wawryszuk-Misztal (2016) found that for companies migrating from NewConnect to the WSE’s regulated market, there is no significant increase in the shareholding of financial institutions.…”
Section: Literature Reviewsupporting
confidence: 54%
See 2 more Smart Citations
“…Such results were confirmed in a broader sample, i.e. 71 companies by Podedworna-Tarnowska and Kaszyński (2022), who showed also the liquidity improvement of shares after the listing switch. Wawryszuk-Misztal (2016) found that for companies migrating from NewConnect to the WSE’s regulated market, there is no significant increase in the shareholding of financial institutions.…”
Section: Literature Reviewsupporting
confidence: 54%
“…, 2021). Studies include the effects of switching from a less regulated to a more regulated market (for example Sanger & McConnell, 1986; Jain & Kim, 2006; Asyngier, 2015; Kwok, 2020; Podedworna-Tarnowska & Kaszyński, 2022) or from more regulated to less regulated markets (e.g. Mortazian, 2022; Bessler et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Amihud and Mendelson (1986), Sanger and McConnell (1986), Baker and Edelman (1992), Kadlec and McConnell (1994), Jain and Kim (2006) confirmed that trading liquidity improves when shares start to be traded on an organized exchange. It was confirmed on the Polish market, as a result of the transfer of companies and the analyzed events preceding the transfer, there is an improvement in the liquidity of the shares (Podedworna-Tarnowska & Kaszyński, 2022).…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 74%
“…Several studies concerning switching companies from a lower trading venue to a more regulated market show that such movement was followed by negative returns in the medium and long term (Sanger & McConnell, 1986;Baker & Edelman 1992;Kadlec & McConnell, 1994;Jain & Kim, 2006;Campbell & Tabner 2011;Vismara et al, 2012, Mortazian, 2022. As mentioned in the introduction, studies of companies' transfers on the Polish market are extremely rare but also confirmed the occurrence of abnormal positive stock returns before the change of listing market and clearly negative ones after the transfer of listing to the regulated market (Asyngier, 2015;Podedworna-Tarnowska & Kaszyński, 2022). Merton (1987) argues that if investors do not have equal information, they invest only in those securities of which they are aware, stocks that have a wide investor base and higher institutional ownership have lower expected returns.…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 98%